2023
DOI: 10.1149/2754-2734/acd800
|View full text |Cite
|
Sign up to set email alerts
|

One Pot Synthesis of CuO-CuFe2O4@rGO Nanostructure with Synergistic Effect for Efficient Electrochemical Sensing Application of Paracetamol

Abstract: In the present study, the facile and synergistic approach for electrochemical sensing of paracetamol (PA) drug was demonstrated by hydrothermally synthesized copper oxide-copper ferrite nanohybrid composite supported on reduced graphene oxide (CuO-CuFe2O4@rGO) glassy carbon electrode. The surface texture and structural information of the electrode material were examined by FE-SEM, HR-TEM, and X-ray diffraction techniques, whereas the electrochemical sensing application of paracetamol oxidation was investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…also used NaCl, KCl, glucose, uric acid, ascorbic acid, and dopamine as the species that can interfere with the PCM analyte and tested them by the amperometric method. According to the data they obtained, it was stated that the species with the potential to interfere show a negligible peak current value [48]. Thus, it has been determined that the studies conducted for GO@YO/GCE are compatible with the literature.…”
Section: Effect Of the Interferencesmentioning
confidence: 57%
“…also used NaCl, KCl, glucose, uric acid, ascorbic acid, and dopamine as the species that can interfere with the PCM analyte and tested them by the amperometric method. According to the data they obtained, it was stated that the species with the potential to interfere show a negligible peak current value [48]. Thus, it has been determined that the studies conducted for GO@YO/GCE are compatible with the literature.…”
Section: Effect Of the Interferencesmentioning
confidence: 57%
“…W. Liang et al fabricated CuFe 2 O 4 for electrical energy storage [46]. J. C. Bhangoji et al identified CuO-CuFe 2 O 4 @rGO for paracetamol sensing [47]. V. Mahdikhah [49].…”
Section: Introductionmentioning
confidence: 99%